Oxidative oligomerisation of methane to aromatics - Claridge, J; Green, M; Tsang, S; York, A (1992)
The temperature, pressure and residence time effects on the reactions of methane and oxygen over an empty silica tube have been studied. It has been found that at elevated pressure and temperature a considerable amount of aromatics (benzene and toluene) is formed. The yield of aromatic products is comparable to that for the gas-phase production of methanol, and is higher than that reported for form-aldehyde. Metal oxide catalysts enhance the selectivity and the yield of aromatics. Thus, chlorine-promoted manganese oxide gives a consistently higher yield of aromatics than the empty tube reactions. However, we are unable to reproduce recent reports of high benzene selectivity over supported nickel catalysts. The mechanisms for the formation of aromatics have been investigated and the possible path-ways are discussed. © 1992.